Does individual attributes matters on the employability readiness among engineering graduates of the higher education institutes in Oman / Masoud Rashid Al Hinai, Abul Bashar Bhuiyan and Nor Azilah Husin - Rashid Al Hinai, Masoud; Bhuiyan, Abul Bashar; Husin, Nor Azilah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The aim of this study is to examine the effects of individual attributes on the Employability Readiness among engineering graduates of the Higher Education Institutes in Oman. The study adopted a self-directed structured questionnaire that was distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used the structural equation modelling (SEM) to analyse the collected data. The findings of the statistical analysis of the study showed that the most influential individual attributes on graduates’ readiness for employability are workshop attendance that affect the attainment of the technical skills of the graduates, family motivations, and graduates’ career orientations that help graduates to identify future career requirements and future career opportunities, and the graduates ’personal learning targets. Additionally, class attendance, academic excellence, financial sources, and parents’ career position showed high important effects as well. The findings consist of the individual attributes of personnel’s values, attitudes, abilities, and work life balance in enhancing the graduates’ attainment of the adaptability and flexibility attributes for their future readiness for employability. Therefore, the findings of the study showed that the Individual attributes factor has a high influence on the Readiness for Employability of the graduates in Oman. Finally, the study’s implementations and recommendations could be used in the Gulf and Arab or other countries’ contexts that have similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.